Hemoglobin, albumin, lymphocyte and platelet (HALP) score for predicting early and late mortality in elderly patients with proximal femur fractures. - Abdussamed Vural; Turgut Dolanbay; Hilal Yagar (PLoS ONE)
Background Predicting mortality and morbidity poses a significant challenge to physicians, leading to the development of various scoring systems. Among these, the hemoglobin, albumin, lymphocyte and platelet (HALP) score evaluates a patient's nutritional and immune status. The primary aim of this study was to determine the predictive effect of the HALP score on 30-day and 1-year mortality in elderly patients with proximal femoral fractures (PFFs). Materials and methods Patient demographic, clinical, laboratory, and prognostic data were obtained. The patients were categorized into two groups: survival and nonsurvival at mortality endpoints. The HALP score was calculated and compared among the groups and with other mortality biomarkers such as C-reactive protein (CRP) and C-reactive protein to albumin ratio (CAR). The ability of the HALP score to predict mortality was compared between the groups. The mortality risk was also calculated at the optimal threshold. Results The HALP score had a statistically significant predictive effect on mortality endpoints and was lower in the non-surviving group. The ability of the HALP score to predict 1-year mortality at the optimal cut-off value (17.975) was superb, with a sensitivity of 0.66 and specificity of 0.86 (AUC: 0.826, 95% CI: 0.784-0.868). In addition, the power of the HALP score to differentiate survivors and non-survivors was more significant than that of other indices (p < 0.001). Patients with a HALP score ≤ 17.975 had a 1-year mortality risk 11.794 times that of patients with a HALP score ≥ 17.975 (Odds ratio: 11.794, 95% CI [7.194-19.338], p < 0.001). Conclusion The results indicate that the HALP score demonstrates efficacy and utility in predicting 30-day and 1-year mortality risk among elderly patients with PFFs.